2014
DOI: 10.15282/jmes.7.2014.4.0102
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Single-Pass/Double-Pass Techniques on Friction Stir Welding of Aluminium

Abstract: The aim of this research is to study the effects of single-pass/ double-pass techniques on friction stir welding of aluminium. Two pieces of AA1100 with a thickness of 6.0 mm were friction stir welded using a CNC milling machine at rotational speeds of 1400 rpm, 1600 rpm and 1800 rpm respectively for single-pass and double-pass. Microstructure observations of the welded area were studied using an optical microscope. The specimens were tested by using a tensile test and Vickers hardness test to evaluate their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…These alloys have excellent corrosion resistance, formability, and weldability [1][2][3][4][5]. Additionally, these alloys are desirable for making components of internal combustion engines such as the cylinder block and head and piston, which are usually subjected to relatively high temperatures during service [6].…”
Section: Introductionmentioning
confidence: 99%
“…These alloys have excellent corrosion resistance, formability, and weldability [1][2][3][4][5]. Additionally, these alloys are desirable for making components of internal combustion engines such as the cylinder block and head and piston, which are usually subjected to relatively high temperatures during service [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is a very challenging process due to the significant difference in the material properties. A lot of research has been done and reported on dissimilar welding [10][11][12]. Arguably the most famous research is on welding between aluminium and steel [2,[13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The method of clamping and its effects on machine processes are well understood. Besides that, clamping claws is an easy and less costly system, however, it leads to varying temperature distributions which could be improved through the use of pressure bars [5][6][7]. Advanced research have indicated that continuous clamping approaches could lead to a more consistent FSW quality along the joint's length [8].…”
Section: Introductionmentioning
confidence: 99%